Implementasi Manajemen Kesehatan dalam Meningkatkan Kualitas dan Ketersediaan Fasilitas Pelayanan Kesehatan - Ayu Anggraeni Dyah Purbasari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Health service management has an important role in managing resources effectively and efficiently, dealing with the dynamics of community needs, and ensuring quality health services through a systematic and humanistic approach. However, there are still shortcomings in the availability of adequate resources and managerial skills of implementing officers in service units that do not meet the standards. This study aims to analyze the direct impact of health management on accessibility, quality, effectiveness, and policy-making in health services.This study uses a literature review method with data sources obtained from Google Scholar, National Library e-Resources, and Garuda Portal. The research data was taken from 2015-2025. Based on the literature review, effective health management includes strategic planning, strengthening internal management, managing human resources, community involvement, and utilizing technology. The implementation of health management is proven to improve the competence of health workers, accelerate service processes, and increase patient satisfaction. In addition, good health management also encourages the expansion of health facility distribution, maintains the availability of drugs and medical devices, and improves the quality of infrastructure. However, there are challenges that need to be overcome, such as limited human resources and challenges in implementing Electronic Medical Records (EMR) in various healthcare facilities. The review shows that health management positively impacts accessibility, service quality, effectiveness, and evidence-based policymaking. Effective strategies include strategic planning, internal managemen human resource management, technology use, and community involvement, although challenges like limited human resources and Electronic Medical Record implementation remain